1986
DOI: 10.1161/01.cir.73.2.347
|View full text |Cite
|
Sign up to set email alerts
|

Acute coronary reocclusion after thrombolysis with recombinant human tissue-type plasminogen activator: prevention by a maintenance infusion.

Abstract: Twenty-nine patients with acute myocardial infarction were treated with recombinant human tissue-type plasminogen activator (rt-PA). The incidence of acute coronary reocclusion and its prevention by a maintenance infusion of rt-PA were studied. Intravenous rt-PA was given at a rate of 0.4 to 0.75 mg/kg over 60 to 120 min after angiographic documentation of complete coronary occlusion. Reperfusion was accomplished within 1 hr in 24 of 29 patients (83%) and was associated with a decrease of the plasma fibrinogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
52
0
1

Year Published

1987
1987
1993
1993

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 304 publications
(55 citation statements)
references
References 24 publications
2
52
0
1
Order By: Relevance
“…Clot lysis and recanalization of the occluded coronary artery induced in vivo by t-PA can be accelerated by adjunctive ther apy with antiplatelet agents such as aspirin or antithrombin agents such as heparin and hiru din (28,29). It has been reported that heparin enhances thrombolysis and maintains coronary artery-patency after the administration of t-PA (6,30). As the balance between fibrin deposi tion and lysis is a key factor for thrombosis, we administered heparin to prevent the forma tion of fibrin and its incorporation into the thrombus during thrombolysis by plasminogen activators.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clot lysis and recanalization of the occluded coronary artery induced in vivo by t-PA can be accelerated by adjunctive ther apy with antiplatelet agents such as aspirin or antithrombin agents such as heparin and hiru din (28,29). It has been reported that heparin enhances thrombolysis and maintains coronary artery-patency after the administration of t-PA (6,30). As the balance between fibrin deposi tion and lysis is a key factor for thrombosis, we administered heparin to prevent the forma tion of fibrin and its incorporation into the thrombus during thrombolysis by plasminogen activators.…”
Section: Discussionmentioning
confidence: 99%
“…This rapid clearance of t PA necessitates intravenous or intracoronary infusion of a relatively high dose in order to maintain therapeutic plasma levels. The rapid decrease in plasma level of t-PA after the ter mination of infusion may result in coronary reocclusion (6), and overdose of t-PA, which may occur with continuous infusion, may in crease the risk of hemorrhagic complications (7) t-PA derivatives with slower clearance from plasma would be effective by intravenous bolus injection and provide advantages over conventional t-PA in the treatment of acute myocardial infarction and other thrombotic diseases. E6010 is a novel modified human t PA, in which cysteine 84 in the epidermal growth factor domain is replaced by serine (8).…”
mentioning
confidence: 99%
“…4 -7 In particular, patients with high-grade (80% or greater) residual stenosis after thrombolytic therapy are considered to be at the greatest risk for acute reocclusion. 8 A number of antiplatelet drugs have been evaluated for their effects on reperfusion and reocclusion by thrombosis or its recurrence.…”
mentioning
confidence: 99%
“…This increases the risk of systemic bleeding, and results in a high incidence of acute reocclusion (1). To eliminate these shortcomings, attempts have been made to modify the t-PA molecule, and several mutants of t-PA that have prolonged plasma half-life and that can be ad ministered by intravenous (i.v.)…”
mentioning
confidence: 99%